The Application of the MOORA Method on Recommendations for Selection of Promotional Media for Nurul Izzah Kindergarten - Siregar, Annisa Fadillah (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2023)
Nurul Izzah Kindergarten is one of the kindergartens located in Deli Tua District, Deli Serdang Regency, North Sumatra. Nurul Izzah Kindergarten has an educational concept of learning either religion or other general education without losing the playful children's world. However, the Deli Tua District community in Deli Serdang Regency is not very familiar with Nurul Izzah Kindergarten, therefore promotion is needed. In this matter, a decision support system is necessary on aiming to recommend the priority of media promotions using the MOORA method. The MOORA method is used to calculate the weight value of each attribute, then the process of which alternative ranking is the most recommended according to the results of the highest Yi calculation, some of these alternatives are Tiktok, Instagram, Facebook, Brochures, and Posters. For recommendations for promotional media, several criteria are required such as the cost, reach, attractiveness, and completeness of information. Based on the calculation of the MOORA (Multi-Objective Optimization based on Ratio Analysis) method for each alternative, the highest Yi is Tiktok with 0.3306 and the second highest Yi is Instagram with 0.2956.